2017
DOI: 10.1186/s12962-017-0073-8
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of the nine-valent HPV vaccine in Italy

Abstract: BackgroundIn Italy HPV vaccination with the quadrivalent vaccine (Gardasil®) is offered actively and free of charge to girls aged 12 since 2007. A nine-valent vaccine (Gardasil 9®) received the European market authorization in 2015 to protect, with only 2 doses, against around 90% of all HPV positive cancers, over 80% of high-grade precancerous lesions and 90% of genital warts caused by HPV types 6/11.MethodsA dynamic transmission model simulating the natural history of HPV-infections was calibrated to the Ita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 39 publications
3
47
1
Order By: Relevance
“…[25][26][27] A later study confirmed the cost-effectiveness of 9vHPV in the United States. 28 In Europe, recent studies in Austria, 29 Germany 30 , Italy 31 and, more recently, in the UK 24 , have also shown the costeffectiveness of 9vHPV in gender-neutral vaccination scenarios.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27] A later study confirmed the cost-effectiveness of 9vHPV in the United States. 28 In Europe, recent studies in Austria, 29 Germany 30 , Italy 31 and, more recently, in the UK 24 , have also shown the costeffectiveness of 9vHPV in gender-neutral vaccination scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the results can be reasonably considered conservative estimates. Finally, our model does not allow running a probabilistic sensitivity analysis; so, as the previously published adaptations [29][30][31] , only deterministic sensitivity analysis was carried out.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome this problem, we recommend the use of a nine-valent vaccine (9vHPV) instead of the bivalent and quadrivalent vaccines. The 9vHPV vaccine contains type 6,11,16,18,31,33,45,52, and 58 which was approved by the FDA in December 2014, and by the European Medicines Agency (EMA) in June 2015 [100].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly when industry sponsored, these models may be considered exercises in marketing rather than science, mainly aimed at supporting prices held high on the basis of various heterogeneous assumptions and estimates open to the authors' discretion and manufacturers' influence [14]; these 'patchwork' analyses are eventually misleading and of scant utility for public policy purposes. The three European economic models focussed on the nonavalent vaccine to support universal coverage that we found in the literature 1 [17][18][19] are no exception and seem more like a further (unnecessary) confirmation of this (mal)practice. All sponsored and co-authored by at least two employees of the manufacturer, the three studies exploited the same American model and concluded that the nonavalent vaccine is cost effective at prices largely over €100 per dose in Austria, Germany and Italy, ignoring in their analyses the much lower prices awarded in domestic tenders for the two other HPV vaccines.…”
Section: Policy Implicationsmentioning
confidence: 76%